Case report: Thromboembolic heartworm induced lower limb necrosis in a dog - Taweethavonsawat, Piyanan; Rattanapinyopituk, Kasem; Tachampa, Kittipong; Kiertkrittikhoon, Srireepong; Jitsamai, Wanarit; Klomkleaw, Wuthichai; Choisunirachon, Nan; Komin, Kiatpichet (Frontiers in Veterinary Science, 2022)
A 9-year-old spayed female boxer suffered from lameness in both hindlimbs with a perforated paw wound. Additionally, a linear, worm-like creature was penetrating out from the wound. On examination, the dog was emaciated and infected with heartworms, detected through a fresh blood smear, echocardiography, and transabdominal ultrasonography. Adult heartworms were detected at the right atrium (RA), right ventricle (RV), and pulmonary artery (PA), including the distal abdominal aorta, external iliac, and femoral arteries. During the surgery, adults heartworms were removed from both the heart (n = 8) and the femoral arteries (n = 5). Unfortunately, not all heartworms could be removed from these locations due to the extent of the heartworm infection. The opened, ischemic wounds in the distal limbs progressively expanded and the dog subsequently died, possibly due to caval syndrome complications and septicemia. The necropsy showed no evidence of an atrial septal defect, and a total of 25 adult heartworms were collected from the perforated paw, heart, pulmonary, and femoral arteries. All worms collected during the necropsy process were molecularly confirmed to be Dirofilaria immitis.